5(-7x-5)-4x=2

Simple and best practice solution for 5(-7x-5)-4x=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(-7x-5)-4x=2 equation:


Simplifying
5(-7x + -5) + -4x = 2

Reorder the terms:
5(-5 + -7x) + -4x = 2
(-5 * 5 + -7x * 5) + -4x = 2
(-25 + -35x) + -4x = 2

Combine like terms: -35x + -4x = -39x
-25 + -39x = 2

Solving
-25 + -39x = 2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '25' to each side of the equation.
-25 + 25 + -39x = 2 + 25

Combine like terms: -25 + 25 = 0
0 + -39x = 2 + 25
-39x = 2 + 25

Combine like terms: 2 + 25 = 27
-39x = 27

Divide each side by '-39'.
x = -0.6923076923

Simplifying
x = -0.6923076923

See similar equations:

| (7c-5)(8c+4)= | | 2(10x-5)-9x=11x+13 | | 4+(10+10)+x=30 | | 5/18=-y/6 | | x+9.3=8 | | n+2=-14-4 | | -7/8t=1/4 | | 7k+2=4x-10 | | 1/5m=9/5 | | -7.6=u/4-1.2 | | 0.20(x+30)+0.20x=10 | | e^7x=3 | | 3/5x+5=7 | | 6/5=2x | | 0.20(x+30)+0.20x= | | x/3=x/4-3 | | (1/x-2)+(x/x+2)=(5/x^2-4) | | 8x+3/7+x-4/4=5 | | -4=-2/5z | | 9x-4(x-1)=8x+22-2x | | 7k+2=4x+22 | | 8/7a=32 | | -2/5y-4/3=5/3y-1 | | 4x-2(1-w)=-38 | | 5a^2-6-7a=0 | | 5x-2(x-9)=3(x+1)+8 | | 3x-14/2 | | 20*x^2=12 | | -2/3=-1/2v-4/5 | | 5(-7x-4)=8x | | 35=23x-12x+5 | | -22.5=-3.3+y/6 |

Equations solver categories